Rancang Bangun Aplikasi Cutting Stock Optimization Dengan Metode Integer Linear Programming Pada Toko Kaca Rejeki - Teguh Wijaya; Yoppy Mirza Maulana; M.J. Dewiyani Sunarto (Jurnal Sistem Informasi Universitas Dinamika, 2014)
Rejeki Glass Shop is one of the stores located in Jl . P.B. Sudirman 186 , Banyuwangi . Rejeki Glass Shop is a store that sells one of the important ingredients in the construction of a building is glass . Glass itself is very diverse , ranging from kind to the thickness of the glass .The problem arises when the order of glass pieces found in large numbers . Order in bulk piece of glass is glass for the windows of the building or the tank . In the cutting process , often resulting inaccuracy in analyzing the pattern. As a result the rest of the glass produced less minimal . It can only be known when calculating and describing the specific , from the patterns to be cut . After the comparison is known that there ineffective and inefficiencies cutting . Problems like this are often referred to as the cutting stock problem .Design Applications Cutting Stock Optimization Methods Integer Linear Programming In Rejeki Glass Shop, is expected to improve the cutting process becomes more effective and efficient . Effective question is about maximizing the broad field of glass , so it can be used optimally. Efficient question is the reduction in material costs that arise from the rest of the glass is wasted